Clinical significance of Osteoprotegerin, Vitamin D, Obestatin and some biochemical variables in Kidney failure Patients - Hazhar M. Balaky; Akam Jasim Mustafa; Parween Abdulsamad Ismail (Iraqi Journal of Pharmaceutical Sciences, 2023)
Chronic kidney disease (CKD) is described as an abnormalities of renal function, existing for a long period of time. By reason of the early grades of Chronic kidney disease can be experiences no symptoms, its premature identification is strenuous. initial stage CRD can cause various complications, such as anemia, matabolyic disorders of bone mineral. The study was done to assess the effect the chronic renal disease stage on the Osteoprotegerin, 1,25 dihydroxyvitamin D, Obestatin levels and some biochemical parameters in patients not undertaken dialysis therapy. In this case-control study fifty-five patients with Kidney failure and fourty healthy people were examined. Circulating concentrations of Osteoprotegerin, 1,25 dihydroxyvitamin D and Obestatin were estimated by ELIZA technique, serum urea, uric acid, total protein and total calciumu were estimated enzymatically using spectrophotometer.Serum concentration of Osteoprotegerin, Obestatin, renal function markers in patients group were higher (328.3±41.68 pg/mL; 15.52±4.28pg/mL; 183.2±10.35 mg/dL; 8.88±0.54 mg/dL; 6.57±0.22 mg/dL) respectively in comparison to the control group (172.6±55.48 pg/mL; 11.64±3.26 pg/mL; 33.45±1.08 mg/dL; 0.95±0.03 mg/dL; 4.35±0.22 mg/dL) respectively. Vitamin D, Total Calcium and Total Proteins level in patients group were lower(24.49±2.53 ng/mL; 8.06±0.18 mg/dL; 6.49±0.12 g/dL) respectively as compared to controls (57.11±12.39 ng/mL; 10.15±0.23 mg/dL; 6.82±0.10 g/dL) respectively. The current study reveals that circulating levels of Osteoprotegerin Obestatin are remarkably linked with the existence of renal failure, the current data identify a high prevalence deficiency and insufficiency of 1,25 dihydroxyvitamin D in patients with moderate and severe Chronic nephropathy.